Characterization of geometrical random uncertainty distribution for a group of patients in radiotherapy (Revista de Física Médica, 2010)
Geometrical random uncertainty in radiotherapy is usually characterized by a unique value in each group of patients. We propose a novel approach based on a statistically accurate characterization of the uncertainty distribution, thus reducing the risk of obtaining potentially unsafe results in CTV-PTV margins or in the selection of correction protocols.